Mechanical harvester removes invasive aquatic weeds to restore water quality and fish habitat values on the Burdekin floodplain. (12th October 2020) - Waltham, Nathan J.; Pyott, Merv; Buelow, Christina; Wearne, Lynise
Abstract : Removal of approximately 5 ha of an aquatic weed in late 2016 rapidly improved water quality in a 7 km section of creek on the Burdekin floodplain, northern Queensland – one of many creeks feeding into the Bowling Green Bay RAMSAR wetland. Numbers of native fish species found in the creek increased from one species prior to treatment to 15 species within 2 years. This project concluded that removal of weed blocks to re‐oxygenate water and improve fish passage is one important action towards improving environmental conditions of floodplains in the Great Barrier Reef catchments, as long as there is ongoing weed follow up.